Budismo tântrico: sexualidade e espiritualidade - Dias, Rafael Parente Ferreira (2018)
This work aims to make an analysis of human sexuality applied to the teachings of Tantric Buddhism. Tantrism seeks in the transmutation of desires and passions a valuable soteriological support capable of emancipating the human consciousness from all psychological conditioning, freeing it from sensory attachments and mental instability. The Tantric method includes in its bulge a great variety of exercises: meditation, visualization and rites. However, one particular technique draws attention to its secret and initiatory character: sex-yoga. Its origins are linked to Siddharta Gautama itself, perpetuating itself in Buddhist communities through the Mahāyāna and Vajrayāna traditions. In order to deepen the teachings of these two lineages, we use some essential texts of the Tantric Buddhist orthodoxy, namely: Guhyasamāja-tantra, Cakraśaṁvaratantra, Hevajra-tantra and Kālacakra-tantra. Besides these, we also rely on the works of important masters of the Vajrayana tradition, such as: Tilopa, Tsongkhapa and Yeshe Tsogyal. In addition, our work is divided into four chapters. In the first chapter we conducted an introductory study on tantra; from the second chapter we enter into a historical investigation into the moment when sexual practices began to be used as tools for spiritual attainment. In the third chapter we delve into the mysteries related to sexyoga and its spiritual effects on the practitioner's body. Subsequently, in the fourth and last chapter, we highlight the centrality of female energy throughout this tantric scenario related to inner transformation. Therefore, we try to demonstrate, throughout the text, that sexual practice is one of the great pillars of Buddhist spirituality, and when performed according to the Tantric teachings it is able to confer the main goal of Buddhism: spiritual enlightenment, ultimate liberation from suffering and of the material judgment.